2021
DOI: 10.1055/a-1311-0859
|View full text |Cite
|
Sign up to set email alerts
|

Gastric peroral endoscopic pyloromyotomy for decompensated gastroparesis: comprehensive motility analysis in relation to treatment outcomes

Abstract: Background and study aims There are no reliable data to predict which patients with gastroparesis (GP) would benefit the most from gastric peroral endoscopic pyloromyotomy (G-POEM). The aim of the present study was to assess whether antro-duodenal motility patterns and pyloric distensibility can predict the outcome of G-POEM in patients with decompensated GP. Patients and methods In an open-label study, patients with GP and refractory symptoms were eligible for treatment with G-POEM if treatment atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Additional applications include assessment of pylorus distensibility before or during gastric peroral endoscopic myotomy (POEM) or surgical pyloromyotomy, estimation of the size of the stoma after gastric band placement, intraoperative assessment for fundoplication tightness and lower esophageal sphincter myotomy adequacy, and as an adjunct to a bougie for measuring the size of the gastric sleeve during a sleeve gastrectomy. [7][8][9] Main components. The FLIP system consists of a 240cm-long, 3-mm-diameter catheter with a highly compliant balloon at the distal end that conforms to the esophageal lumen (Table 1).…”
Section: Technology Under Review Functional Luminal Imaging Probementioning
confidence: 99%
“…Additional applications include assessment of pylorus distensibility before or during gastric peroral endoscopic myotomy (POEM) or surgical pyloromyotomy, estimation of the size of the stoma after gastric band placement, intraoperative assessment for fundoplication tightness and lower esophageal sphincter myotomy adequacy, and as an adjunct to a bougie for measuring the size of the gastric sleeve during a sleeve gastrectomy. [7][8][9] Main components. The FLIP system consists of a 240cm-long, 3-mm-diameter catheter with a highly compliant balloon at the distal end that conforms to the esophageal lumen (Table 1).…”
Section: Technology Under Review Functional Luminal Imaging Probementioning
confidence: 99%
“…Therefore, we included 10 studies comprising 482 patients in our meta-analysis. [21][22][23]26,[28][29][30][31][32][33] Of these, three [21][22][23] with 151 patients were prospective and seven 26,[28][29][30][31][32][33] with 331 patients were retrospective. Eight studies with 428 patients reported data on our primary outcome of interest.…”
Section: Re Sultsmentioning
confidence: 99%
“…More recent studies with longer follow-up have evaluated the efficacy of G-POEM. [21][22][23] In this systematic review and meta-analysis, we have evaluated the mid-term efficacy of G-POEM by only including studies with a minimum of 1 year of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Conchillo et al [ 18 ] published a very interesting study with 24 patients (100% technical success rate) to investigate the role of antroduodenal motility pattern and EndoFLIP in predicting the outcome after GPOEM: Clinical response was not correlated with motility pattern, whereas was associated with the pyloric distensibility improvement. However, there are no yet parameters that can surely predict the clinical response after GPOEM[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%